Retained Fetal Membranes in a Marwadi Mare: A Case Report - Kapadiya, FM; Suthar, VS; Patel, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Placenta has been defined as “An apposition between maternal and fetal tissue to establish physiological  exchange” (Mossman, 1937). The review of the literature  indicates that membranes should be considered as retained  if they are not delivered within three hours of parturition,  although there is no particular scientific basis to this time  frame in mares. The etiology of this problem varies from  abortion, dystocia, prolonged gestation, cesarean section,  fetotomy, hydropsy, induced delivery to many other plausible  factors (Provencher et al., 1988; Frazer, 2003; Parmar et al., 2018). A retained fetal membrane (RFM) is the most common  postpartum problem in draft mares (Cuervo-Arango and  Newcombe, 2009; Dinuka et al., 2018); however, the reported  incidence of RFM in Marwadi mares is rare, and recently it was  published in a Kathiawadi mare (Patel et al., 2018). It is well  documented that RFM is a medical emergency as far as risks  of metritis, laminitis, fertility are concerned. In extreme cases,  it also leads to death. Therefore, different treatment regimens  such as oxytocin, antimicrobial therapy, uterine lavage,  Burne’s technique, etc. were developed by practitioners and  practiced globally to solve the issue (Provencher et al., 1988;  Coutinho da Silva, 2016).
Keywords: Manual removal; Marwadi Mare; Retained fetal membranes